ANALISIS FAKTOR PENYEBAB KESALAHAN PEMBERIAN NOMOR REKAM MEDIS OLEH PETUGAS PENDAFTARAN DI PUSKESMAS KOTAANYAR - Kustiana Dewi Sugiarti; Dea Allan Karunia Sakti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
Kotaanyar Public Health Center uses done the Unit Numbering System numbering, manually and computerized. The registration officer at the Kotaanyar Health Center often makes mistakes in the patient registration process, the officer gives the wrong medical record number, forgets to cross out the medical record number due to lack of concentration. This causes several impacts, one of which is duplication of medical record numbers. This type of qualitative research with registration officers as informants. The results showed that the factors that caused errors in giving medical record numbers by the registration officer at the Kotaanyar Health Center were education, facilities and infrastructure, work stress and motivation. Sulu recommendations that can be done are training for registration officers, recruiting registration officers at least D3 Medical Record graduates, maintaining and checking systems or computers in stages, division of tasks between registration officers, and unifying the contents of multiple medical record documents.